Combustion of Pelletized Coffee Residues for Bioenergy Valorization Within a Circular Economy Vision - Vincenzo Civitarese; Angelo Del Giudice; Andrea Acampora; Elisa Fischetti; Thomas Gasperini; Carmine De Francesco; Giuseppe Toscano; Antonio Scarfone (Energies)
Coffee is one of the most widely consumed beverages in the world; the European Union alone consumes about 2.5 million tons of coffee per year. Yearly, millions of tons of coffee residues are generated, becoming an attractive material for circular economy flows. This study explores the potential of utilizing pelletized coffee residues as sustainable bioenergy sources within the framework of a circular economy. The coffee residues, obtained from damaged capsules and pods from factories, were utilized in pure form or blended with sawdust at different percentages, then analyzed with respect to their physical and thermochemical parameters. The results indicate that unblended coffee residues exhibit favorable combustion properties with respect to heating value (18.84 MJ kg−1), but also high concentrations of N (4.14%) compared to the conventional pellets obtained from other agricultural residues. The blending with woody material negatively affects both durability and bulk density, but simultaneously promotes a reduction in ash content (3.09%) and N content (1.94%). In general, this study confirmed the findings of previous scientific reports, highlighting that at least 50% blending with low-nitrogen biomasses is necessary to reach the marketability of the product. In addition, this study highlighted the criticality in terms of durability that these mixtures confer to the final product, emphasizing that future research should focus on optimizing the combination of these factors to improve the properties of the pellet.